2016
DOI: 10.3171/2015.10.focus15441
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic stabilization for L4–5 spondylolisthesis: comparison with minimally invasive transforaminal lumbar interbody fusion with more than 2 years of follow-up

Abstract: OBJECTIVE In the past decade, dynamic stabilization has been an emerging option of surgical treatment for lumbar spondylosis. However, the application of this dynamic construct for mild spondylolisthesis and its clinical outcomes remain uncertain. This study aimed to compare the outcomes of Dynesys dynamic stabilization (DDS) with minimally invasive transforaminal lumbar interbody fusion (MI-TLIF) for the management of single-level spondylolisthesis at L4–5. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 32 publications
0
24
0
Order By: Relevance
“…There is an abundance of literature regarding traditional, non-hybrid Dynesys instrumentation and its associated complications [ 26 - 27 ]. Infection rates have been generally well controlled during these procedures [ 12 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is an abundance of literature regarding traditional, non-hybrid Dynesys instrumentation and its associated complications [ 26 - 27 ]. Infection rates have been generally well controlled during these procedures [ 12 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The inclusion criteria were involvement of two or more lumbar segments, neurogenic claudication caused by lumbar spinal stenosis, or low back or leg pain caused by degenerative intervertebral disc disease. 4 6 The exclusion criteria were severe osteoporosis; severe spinal deformity; grade ≥2 lumbar degenerative spondylolisthesis; progressive intervertebral disc degeneration; serious instability associated with lumbar spine disease; obesity (body mass index of ≥30 kg/m 2 ); serious heart, brain, or lung disease; trauma; infection; malignant tumors; history of lumbar spine surgery; and pelvic-related disease.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, patients with immobile segmental motion (< 3°) on lateral dynamic radiographs would have been recommended for fusion procedures rather than DDS. Surprisingly, in our series of DDS, 4,6,[12][13][14]28,29 a substantial portion of the patients who underwent dynamic stabilization ended up with little segmental mobility and were found to have the facets fused. Therefore, the present study was designed to demonstrate that spondylolisthesis could be a risk factor of the limited segmental mobility found after DDS, although DDS was originally designed for preservation of motion and avoidance of fusion.…”
Section: Discussionmentioning
confidence: 57%
“…We conducted studies to compare lumbar fusion with dynamic stabilization with an average follow-up of more than 2 years. 14,15 Kuo et al first examined 86 patients with L4-5 spondylolisthesis and demonstrated that the clinical and radiological outcomes of DDS were similar to those of minimally invasive transforaminal lumbar interbody fusion (mi-TLIF) for grade I spondylolisthesis after approximately 2.5 years postoperatively. Although DDS might be an alternative to standard arthrodesis in mild lumbar spondylolisthesis, the dynamic pedicle screws could have other issues like wearing and loosening in long-term follow-up.…”
Section: Discussionmentioning
confidence: 99%